Describing How School-Based SLPs Determine Eligibility for Children with Speech Sound Disorders - Farquharson, Kelly; Tambyraja, Sherine R. (Seminars in Speech and Language, 2019)
The purpose of this study was to explore how school-based speech–language pathologists (SLPs) determine eligibility for children with speech sound disorders (SSDs). Presently, there is substantial variability nationwide with respect to if or how children with SSDs receive speech therapy in public schools. We report the results of a nation-wide survey of school-based SLPs, which further underscore this variability. Findings provide insight into which and how many factors SLPs report contributing to eligibility decisions, as well as which and how many components of an assessment are mandatory. Our discussion includes a call to advocacy for SLPs, but also a need for increased awareness of this problematic variability for school administrators.
Keywords: speech sound disorders; IDEA; school-based practice; assessment